Pengabdian Kepada Masyarakat Manfaat Gizi Seimbang Bagi Kesehatan: Pengabdian - Betty Sunaryanti (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Elderly is a process in the stages of life which is usually associated with a decrease in individual power or ability to live and sensitivity. One aspect that plays a big role in maintaining the health of the elderly is a balanced diet or nutrition. Balanced nutrition is a daily food composition that contains nutrients in types and quantities that suit the body's needs, taking into account the principles of food diversity, physical activity, clean living behavior and maintaining body weight regularly in order to maintain a normal body weight to prevent nutritional problems. . Efforts to educate and monitor balanced nutrition are very necessary. The main aim of this counseling is to increase the understanding of PKK (Family Welfare Empowerment) mothers about the importance of the benefits of balanced nutrition for health. Education is through lectures and discussions about the benefits of balanced nutrition. The target of the activity is PKK participants.The results show an increase in health and understanding of balanced nutrition.